Prokrastinasi Akademik Ditinjau Dari Manajemen Waktu Dan Conscientiousness Pada Mahasiswa Di Kabupaten Karawang - Guntara, Davina Alifia; Sadijah, Nur Ainy; Mustika, Haryanti (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2026)
This study aims to determine the influence of time management and conscientiousness on academic procrastination in students in Karawang Regency. The research method used is quantitative with a comparative causality design. The population in this study is students in Karawang Regency with a sample of 399 respondents obtained through snowball sampling techniques. The instruments used include the Time Management Questionnaire (TMQ) to measure time management, the Big Five Inventory-2 (BFI-2) in the domain of conscientiousness, and the Tuckman Procrastination Scale (TPS) to measure academic procrastination. Data analysis was carried out using multiple regression tests (t-test and F-test) with the help of SPSS software version 26.0 for Windows. The results showed that only conscientiousness had a significant effect on academic procrastination, while time management did not show a significant effect. But simultaneously, time management and conscientiousness have a significant influence on academic procrastination. The value of the determination coefficient showed that the two independent variables were able to explain 77.3% of the variation in academic procrastination. Theoretically, these findings reinforce the study of personality psychology that emphasizes the role of trait conscientiousness as an important factor in controlling academic procrastination behavior. Practically, the results of this research can be the basis for universities to design character development programs, self-management training, and psychological interventions that focus on increasing conscientiousness to reduce the tendency of academic procrastination in students. Keywords:Academic Procrastination, Time Management, Conscientiousness, Students